MOOCs in Research Methodology for Universities in Ecuador - Leal Maridueña, Isabel Amarilis (2023)
It is imperative that universities incorporate ICT in their teaching and learning processes because now more than ever it is a fact that we live in the "Age of the information and interaction society", where information and communication technologies play Its determining role The general objective of this work was to create an online MOOC course with an expected learning model for undergraduate and postgraduate students. This work will encourage UNEMI to overcome limits that only apply to the education of professionals through face-to-face training systems and will adopt them in the near future in mixed learning environments that open the way to new paradigms that consider principles epistemological, ontological, ethical, political and educational. The general objective of this research was to propose a massive open online course MOOC for Research Methodology. Said course was born from the investigation of Didactic Strategies to improve the attitude towards research of students of a university in the province of Guayas, Ecuador. This work contributes to massify research at the university by using ICT as a means to change traditional face-to-face learning environments into virtual learning environments. The results obtained allow us to say with all seriousness that they have been positive, managing to educate a large group of students and teachers from an Ecuadorian university.